Impact of Online Reviews, Pricing, and Viral Marketing on Shopee Purchases - Nita Anggraini; Hasan Ubaidillah (Universitas Muhammadiyah Sidoarjo, 2024)
This study investigates the influence of Online Consumer Review (X1), Price (X2), and Viral Marketing (X3) on Purchase Decisions (Y) on Shopee among students of the Faculty of Business, Law, and Social Sciences at the University of Muhammadiyah Sidoarjo. Utilizing quantitative methods and IBM SPSS Version 25 for analysis, data was collected through survey questionnaires from 110 students selected via purposive sampling. Results indicate that Online Consumer Reviews, Price, and Viral Marketing significantly impact Purchase Decisions on Shopee. The findings underscore the importance of these factors in shaping consumer behavior on e-commerce platforms like Shopee, suggesting practical implications for businesses to optimize these aspects for enhanced consumer engagement and decision-making processes. Future research should explore additional variables and expand sample sizes to further enrich understanding of online consumer behavior. Higlight: Factor Influence: Reviews, pricing, viral marketing significantly affect purchase decisions. Quantitative Approach: SPSS utilized for rigorous data analysis. Business Insights: Study offers practical strategies for enhancing online engagement. Keywoard: Online Consumer Reviews, Price, Viral Marketing, Purchase Decisions, E-commerce Platforms